Inflation and Monetary Policy – What Next? - Lydon, Reamonn (Statistical and Social Inquiry Society of Ireland, 2023)
A combination of pandemic-related bottlenecks, strong demand and the war in Ukraine have contributed to record-high rates of inflation in the euro area and Ireland. Since the late-2022 inflation peak, headline inflation has started to decline, partly as a result of falling energy prices. However, underlying and core measures of inflation remain elevated and, until there is a clear shift in momentum in these metrics, policy makers are likely to see this as a potential upside risk to medium term inflation dynamics. Going forward, wage and profit developments, as well as evidence on the transmission of monetary policy to the real economy, will be key to calibrating the future path for monetary policy. Household resilience has been tested by large price increases and rising interest rates. Evidence suggests that to-date, inflation has been relatively more burdensome for households, especially for those with limited savings and where energy and food spending was already a significant share of their spending.
Cost of Living Symposium (read before the Society, 8th December 2022)
Keywords: inflation; monetary policy transmission; interest rates; distribution of income and wealth; 314.15